Airway Microbiota in Bronchoalveolar Lavage Fluid from Clinically Well Infants with Cystic Fibrosis - Laguna, Theresa A. (PLoS One, 2016)
BACKGROUND: Upper airway cultures guide the identification and treatment of lung pathogens in infants with cystic fibrosis (CF); however, this may not fully reflect the spectrum of bacteria present in the lower airway. Our objectives were to characterize the airway microbiota using bronchoalveolar lavage fluid (BALF) from asymptomatic CF infants during the first year of life and to investigate the relationship between BALF microbiota, standard culture and clinical characteristics. METHODS: BALF, nasopharyngeal (NP) culture and infant pulmonary function testing data were collected at 6 months and one year of age during periods of clinical stability from infants diagnosed with CF by newborn screening. BALF was analyzed for total bacterial load by qPCR and for bacterial community composition by 16S ribosomal RNA sequencing. Clinical characteristics and standard BALF and NP culture results were recorded over five years of longitudinal follow-up. RESULTS: 12 BALF samples were collected from 8 infants with CF. Streptococcus, Burkholderia, Prevotella, Haemophilus, Porphyromonas, and Veillonella had the highest median relative abundance in infant CF BALF. Two of the 3 infants with repeat BALF had changes in their microbial communities over six months (Morisita-Horn diversity index 0.36, 0.38). Although there was excellent percent agreement between standard NP and BALF cultures, these techniques did not routinely detect all bacteria identified by sequencing. CONCLUSIONS: BALF in asymptomatic CF infants contains complex microbiota, often missed by traditional culture of airway secretions. Anaerobic bacteria are commonly found in the lower airways of CF infants.